GROWTH, SURVIVAL AND PRODUCTION OF Penaeus monodon AND OTHER SPECIES IN INTEGRATED MULTITROPHIC AQUACULTURE PONDS - Arriesgado, Elgen M.; Arriesgado, Dan; Fagutao, Fernand; Choresca, Cassiano Jr.; Anuevo, Gwen; Pedroso, Fiona (Indonesian Aquaculture Journal, 2024)
The growth and survival of Penaeus monodon and other commercial species and the production performance of Integrated Multitrophic Aquaculture (IMTA) system were evaluated in a 500 m2 experimental grow-out ponds of Mindanao State University at Naawan for 120 days. Three triplicated treatments, monoculture (P. monodon only), polyculture (P. monodon and Chanos chanos) and IMTA (P. monodon, C. chanos, Perna viridis and Gracilaria verrucosa) were evaluated in a semi-intensive pond culture operation. Salinity (24.3 to 34.36‰), temperature (28 to 40.64°C) and pH (7.5 to 9.49) exceeded the maximum ideal limit for the cultured organisms in all treatments. Dissolved oxygen levels (2.76-5.43) were within the optimal range of some cultured organisms. Growth of shrimp (5.33±0.02 %SGR P <0.05) and milkfish (4.49±0.03 %SGR P <0.05) were significantly better in IMTA than in polyculture. Shrimp’s survival was also significantly higher in IMTA (24.13%±3.95, P <0.05) than in the other treatments. Shrimp-milkfish biomass was highest in IMTA (89.67 kg), followed by polyculture (57.72 kg) and lowest in monoculture (11.33 kg). The higher biomass and survival of shrimp and milkfish in IMTA ponds could be attributed to the cultured organisms' synergistic interaction, such as shading and nutrient remediation by G. verrucosa and bioremediation by P. viridis. Revenue and profit followed a similar trend, with IMTA revealing profitability over the polyculture and monoculture. Hence, the results demonstrate the efficiency of the IMTA systems over monoculture and polyculture in the growth and survival of the high-valued jumbo tiger shrimp, P. monodon and the overall production and profitability.